Sabah dalam konteks pembinaan nasion Malaysia prosiding Seminar Kebangsaan Pembinaan Nasion Malaysia 2003 - Mohd. Sarim Haji Mustajab; Raman, G. Anantha (Govindasamy Anantha) (Unit Penerbitan, Universiti Malaysia Sabah, 2004)
Historical, political, economic, linguistic, and cultural aspects of Sabah since 1963 towards national development in Malaysia; papers